An Integration Approach for Distributed Education with Lecture, Project, Problem and Work Based Learning - Akarsu, Busra; Parlak, Koray Sener; Karakose, Mehmet (Ieee, 2016)
People have developed various ways to continue and ease their lives and to learn what they wonder about since the early ages. The development of technology has provided people with the opportunity to obtain information easily and fast. However, people need to have not only information but also other skills to do something. Therefore, the aim of higher education is to make students gain knowledge and skills necessary for her/his career with different approaches. The study is based on helping students accommodate themselves to business life, as it is the case for many systems. In order to achieve this, the student must gain autonomous learning skill. The student can acquire this skill by overcoming a problem that s/he can face in real life. However, s/he cannot solve such a problem without learning the basics. For this reason, it can be ensured that the student learns the basics by being instructed and, in parallel with the courses, acquires the desired skills with a problem that can be faced in real life in the suggested system. The students who have the basics can decide more comfortably with respect to what they know for the project and what they must learn. People cannot work by themselves in business life. This shows that students must acquire both autonomous learning skill and the skill for competition. In order for the students to acquire these skills, the classroom should be divided in two or more groups and the groups who are assigned with the same tasks must be observed. Observing only the groups prevents learning how much each student contributes to the group. It is difficult to control every student one by one. Every group has a platform in the system. With this platform, both the instructor will see how each student works easily and the students can take part in the project whenever they want without any time and place limitations or can share information with their friends. The instructor will be able to understand how much all the students contribute to the project more easily by accessing all the platforms.
15th International Conference on Information Technology Based Higher Education and Training (ITHET) -- SEP 08-10, 2016 -- Istanbul, TURKEY
Keywords: Distributed Education; Lecture Based Learning; Problem Based Learning; Project Based Learning; Work Based Learning; Cased Based Learning